DIRECT AND INDIRECT EFFECT OF BRAND CREDIBILITY, BRAND COMMITMENT AND LOYALTY INTENTIONS ON BRAND EQUITY - Veeva Mathew; Sam Thomas; Joseph I Injodey (Economic Review)
Brand equity has been and will be an area of interest for marketing managers. All marketing efforts are directed toward the development of brand equity. Therefore efforts are taken among the researchers, to understand the concept of brand equity as deep as possible. This paper attempts to understand the interrelationships among key  formative indicators of brand equity, using belief-attitude-intention hierarchy of effects. The formative indicators include brand credibility, brand commitment, and loyalty intentions. Using Sequential Chi-square Difference Test in Structural Equations Modelling, the researchers identified the mediating role of brand commitment and loyalty intentions, in the formation of brand equity.